Plasticity and geomechanics - Davis, R. O. (Cambridge University Press, 2002)
Plasticity theory is widely used to describe the behaviour of soil and rock in many engineering situations. Plasticity and Geomechanics presents a concise introduction to the general subject of plasticity with a particular emphasis on applications in geomechanics. Derived from the authors' own lecture notes, this book is written with students firmly in mind. Excessive use of mathematical methods is avoided in the main body of the text and, where possible, physical interpretations are given for important concepts. In this way the authors present a clear introduction to the complex ideas and concepts of plasticity as well as demonstrating how this developing subject is of critical importance to geomechanics and geotechnical engineering. This book therefore complements Elasticity and Geomechanics by the same authors and will appeal to graduate students and researchers in the fields of soil mechanics, foundation engineering, and geomechanics.